Continual description of polycrystalline systems taking into account their structure - Kuzin, Oleg; Lukiyanets, Bohdan; Kuzin, Nikolay (Technology audit and production reserves, 2018)
The object of research is the behavior of grain boundaries, the conditions for the formation of intergranular damage and intercrystalline destruction of polycrystalline alloys under the influence of force loads. The problem of creating internal boundary zones with given thermodynamic, physical and mechanical characteristics in alloys, the solution of which is the most promising way to improve their properties, requires the use of mathematical modeling methods. It is allow one to quantify the influence of chemical composition, heat treatment and external loads on the formation of intergranular damage to polycrystalline systems. In the course of research based on the energy approach of describing continual media taking into account physical effects occurring on a scale commensurate with the structural components and their boundaries, the mathematical relationships of the model of polycrystalline systems are constructed. This model is the basis for calculations and establishing the stress-strain state of the material at the meso level. It is shown that the mechanical behavior of materials is influenced not only by the absolute values of the parameters of the properties of individual microvolumes of bodies, but also by their gradient. The relationship between the presence of grain boundaries in improved steels with an increased level of energy and the ability to form intergranular damage when exposed to an external load is obtained. A conceptual approach has been developed to control the properties of the internal surfaces of the alloy section by changing their structural-energy state. This is due to the fact that the proposed model and experimental dependencies are based on a physically reasonable parameter – the relative property gradient, which determines the segregation of impurities and the separation of phases by the density of dislocations in the boundary zones of the grains. The limiting values of the characteristics of local volumes of grains, at which the ability to form intergranular damage and intercrystallite destruction of alloys, is established. This ensures the possibility of introducing innovative technologies of grain-boundary design of the structure of metal products. It is makes possible to significantly increase the reliability parameters of machine parts in comparison with the known technologies – durability, service life, reliability with minimal economic costs.